THE RELATIONSHIP BETWEEN PARENTS SUPPORT AND LEARNING MOTIVATION IN ADOLESCENTS DURING THE PANDEMIC PERIOD AT SMPN 2 PULE TRENGGALEK - Hidah Rohmahwati; Yati Sri Hayati; Niko Dima Kristianingrum (Universitas Brawijaya, 2021)
The Covid-19 pandemic has an impact on all aspects of life, including the implementation of learning activities that are changed from face-to-face to distance learning. Distance learning requires student independence which needs to be encouraged by a high motivation to achieve learning success. Parents as a substitute for teachers at home are expected to provide optimal support so that adolescents have high motivation to learn while participating in learning activities. This study aims to determine the relationship between parental support and learning motivation in adolescents during the pandemic period at SMPN 2 Pule Trenggalek. This was an observational study using a cross-sectional design. Respondents in this study are students of SMPN 2 Pule Trenggalek Class VIII and IX, totaling 142 students, who are selected based on simple random sampling techniques. This study uses an online questionnaire about parental support and student motivation during the pandemic as a means of collecting data. The results showed the majority of parental support was in the high category (95.8 %), and the respondents learned motivation was in the medium category (54.2%). The results of data analysis using the Spearman rank obtained a correlation value of 0.361 with a p-value of 0.000 so that Ho was rejected (<0.05). The study concludes that there is a relationship between parental support and learning motivation in adolescents during distance learning in the pandemic period at SMPN 2 Pule Trenggalek. Further research can be carried out related to parental support provided to adolescents during the pandemic with parents as respondents so that the data obtained will be comprehensive.